Laser-induced quenching of the Th-229 nuclear clock isomer in calcium fluoride - F. Schaden; T. Riebner; I. Morawetz; L. Toscani De Col; G. A. Kazakov; K. Beeks; T. Sikorsky; T. Schumm; K. Zhang; V. Lal; G. Zitzer; J. Tiedau; et al. (Physical Review Research)
The 10-min radiative lifetime of the first excited ^{229}Th^{4+} nuclear state in ionic crystals provides narrow spectroscopic linewidths, enabling the realization of a solid-state nuclear clock. Due to the 4+ noble gas configuration, electronic readout or state initialization schemes known from atomic clocks are inaccessible. This elongates the interrogation cycle, which will deteriorate the clock performance. To address this limitation we demonstrate laser-induced quenching (LIQ) as a method of depumping the ^{229}Th isomer population in CaF_{2}. We provide experimental evidence for LIQ at different wavelengths (148–420 nm) and temperatures (100–350 K), achieving a threefold reduction in the isomer lifetime with 20 mW of laser power.